Inefficacy of Hydroxychoroquine in Primary Sjögren's Syndrome: Results of the JOQUER Trial - Vinall, Maria (MD Conference Express, 2012)
The Hydroxychloroquine Versus Placebo in Primary Sjögren's Syndrome [JOQUER; NCT00632866] trial found no significant difference in the evolution of systemic disease activity, dryness, symptoms, and quality of life in patients treated with hydroxychloroquine when compared with placebo.